Monologika; Retorika untuk Tabligh Islam (Menelusuri sejarah menemukan arah) - Aang Ridwan (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2009)
Retorika has the significant position  in oftimalizing  tabligh's aim attainment. The top aspect of tabligh that utilizes rhetorics can be recognized on mubaligh’s skill in getting language and managing knowledge that will be passed to audiences  so tabligh's message becomes sistematic. In developing history of the monologic's rhetoric has recognized three forms of rhetorics, there are elocusionis ,  Belles lettris , and teste faculty. (1 )  elocusionis, focusing its study on technic problem of oration forwarding, (2 ) Belletrist, this rhetoric form  really accentuates aesthetical lingual and esthetic facet order on writing. (3 ) teste faculty rhetorics, it emphasize teste importance in rhetoric.